Optimizing method parameters for ion pair-based high performance liquid chromatographic analysis (IP-HPLC) for complex amine blend formulas used in post combustion carbon dioxide capture. (January 2016) - Supap, Teeradet; Idem, Raphael; Gelowitz, Don; Campbell, Colin; Ball, Max
Highlights: Ion-pair based HPLC is developed for complex amine blend separation. Heterocyclic amines with 2 amino sites are separated at pH between their 2 p K a s. Isocratic and pH step gradient conditions for amine separation are developed. Abstract: The objective of this work was to develop the ion pair based high performance liquid chromatographic technique (IP-HPLC) to analyze various carbon dioxide (CO2 ) capture amine solvent blends. This work developed pH step gradient conditions with isocratic conditions using a combination of 5-mM perfluoroheptanoic acid (PFHA), 0.3 M ammonium acetate and acetonitrile (ACN) at various pH with that were able to separate blends containing monoethanolamine (MEA), diethanolamine (DEA), and methyldiethanolamine (MDEA), 2-methyl-2-amino-1-propanol (AMP), piperazine (PZ), 1-(2-hydroxyethyl)piperazine (HEP), 1-(3-hydroxypropyl)piperazine (HPP), 1, 4-bis(2-hydroxyethyl)piperazine (BHP). The key feature responsible for separating the amines, especially the heterocyclic amines containing 2 amino sites, is the adjustment of the separation pH between the amines' 2 p K a 's. Possible amine blends that can be analyzed by the technique include MEA-MDEA, MEA-AMP, MEA-BHP, MEA-HPP, MEA-AMP, HEP-HPP, DEA-BHP, DEA-HEP, DEA-AMP, MEA-PZ, MDEA-PZ, AMP-PZ, MEA-AMP-PZ. With the pH step gradient conditions, industrial amine mixtures including those containing heterocyclic amines such as PZ can be separated and analyzed.